تحولات سوق الغاز الأوروبي بعد حرب روسيا-أوكرانيا ومكانة الغاز الجزائري اتجاه المنافسين: The transformations of the European gas market after the Russia-Ukraine war and the position of Algerian gas towards competitors - عبد الحميد رولامي (Journal of North African Economies, 2025)
The study aims to shed light on the most important developments that have occurred in the natural gas market in Europe after the Russia-Ukraine war, by analyzing data from the seven largest gas-consuming countries in Europe (France, Germany, Italy, the Netherlands, Spain, Turkey, and the United Kingdom) during the period from 1970 to the end of the first half of 2022. The study also highlights the impact of these developments on the natural gas industry in Algeria, based on the analysis of two important indicators: the first indicator is the flexibility of alternatives to Russian gas, which are the countries that export gas through pipelines and liquefied gas together; and the countries that export liquefied gas only. While the second indicator is the acceleration of the shares of these suppliers during the substitution period.. The study concluded that countries exporting only LNG (Qatar, the United States, Nigeria) are more flexible than countries exporting pipeline gas and LNG together (Norway, Algeria, Libya, Kazakhstan) at rates of 0.93 and 0.39, respectively, which means that the gap between them has exceeded 250%. The research paper also concluded that the effects of this war will have positive impacts on the Algerian natural gas industry, including: firstly, long-term gas contracts, especially in terms of the "take or pay" principle, secondly, natural gas prices, thirdly, the source sectors, and fourthly, the LNG industry.